PENGARUH METODE EKSTRAKSI TERHADAP KADAR TOTAL FENOLIK, KADAR TOTAL FLAVONOID DAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN MENGKUDU (Morinda citrifolia L.) - Septiana Laksmi Ramayani; Eka Amalia Permatasari; Indah Novitasari; Maryana Maryana (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
ABSTRACT Excessive Reactive Oxygen Species (ROS) can cause hypertension. Prevention of the risk of hypertension is consume an antioxidant. Noni (Morinda citrifolia L). is a plant that empirically proven to lower blood pressure and has antioxidant activity. Antihypertensive activity of noni leaves is influenced by phenolic and flavonoid compounds. The extraction method affects the levels of compound in extracts. The aims of study is determine the effect of the extraction method on the total phenolic level, total flavonoid level and antioxidant activity of noni leaf extract. The extraction methods are maceration, Microwave Assisted Extraction and Soxhlet. The results showed that the different extraction methods affected the total phenol level, total flavonoid level and antioxidant activity of the noni leaf extract. The Soxlet method provides the highest total phenolic level, total flavonoid level and antioxidant activity than other extraction methods. Keywords: Noni leaf extract, extraction method, total phenolic level, total flavonoid level and antioxidant activity